An Argument from Comparative Law in the Jurisprudence of the Polish Constitutional Tribunal1 - Paprocka, Ada (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The use of references to foreign law and jurisprudence by the constitutional courts around the world currently gains more and more attention from scholars. The admis-sibility and usefulness of conducting such a horizontal dialogue between various juris-dictions raises controversies in other countries, but not in Poland, where no significant academic discussion on the legal basis and justification for using comparative arguments in constitutional jurisprudence has been conducted. The reasons for this lack of contro-versy seem to lie in the roots of the 1997 Constitution, and the way in which the Polish legal system is constructed. The Polish Constitutional Tribunal is quite prone to using comparative references in its reasoning. However, it rarely clearly indicated their role or significance for the resolution of the case before it. The analysis of the case-law of the Tribunal indicates that references to foreign law concern constitutional provisions, legislation, and the judgments of other constitutional courts. The purpose of the refer-ences stresses the universality of particular constitutional norms and deciphering their meaning, as well as gathering data significant for the assessment of the proportionality of a national law, as well as at drawing inspiration from the decisions taken by foreign courts. However, the persuasive use of a comparative argument demands that the meth-odological problems which can be noticed in the case-law should be addressed. They in-volve in particular: the need to justify the choice of comparative material that is analysed, the fragmented nature of the analysis, and the lack of a clear indication what role these kind of arguments have in constitutional argumentation.